Model Reciprocal Teaching untuk Meningkatkan Kemampuan Komunikasi pada Soal Cerita Matematika - Rustam Bunyamin Kapa; Retno Marsitin; Tatik Retno Murniasih (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2023)
This study aims to describe the reciprocal teaching which can improve students’ communication skills on math story problems at SMP Negeri 1 Pakisaji. This type of research is clasroom action research with a qualitative approach. The instruments is activity observation sheets, student activity observation sheets, field notes, interview guidelines and test questions. The data analysis uses qualitative methods, namely reduction, presentation, and conclusions. Based on the result of the study, it can be concluded that reciprocal teaching can improve students’ communication skkls on math story problems for SMP Negeri 1 Pakisaji.